Peripheral Lipopolyssacharide Rapidly Silences REM-Active LHGABA Neurons - Borniger, Jeremy C.; de Lecea, Luis (Frontiers in Behavioral Neuroscience, 2021)
Immune factors (e.g., cytokines, chemokines) can alter the activity of neuronal circuits to promote ‘sickness behavior’, a suite of adaptive actions that organisms exhibit in response to infection/injury in order to maximize their chances of recovery (i.e., return to homeostasis). This includes drastic alterations in sleep/wake states, locomotor activity, and food intake, among other behaviors. Despite the ample evidence highlighting interactions between the brain and systemic immunity, studies on how immune challenges alter the activity of genetically defined cell populations controlling arousal states are scarce. As the lateral hypothalamus (LH) serves a major integrative function in behavioral arousal, food intake, and monitoring and responding to changes in systemic physiology, we investigated how GABAergic neurons within this brain region alter their activity across normal sleep/wake states and in response to a peripheral immune challenge with bacterial endotoxin (lipopolysaccharides (LPS)). Using fiber photometry (GCaMP6s Ca2+ signal) in tandem with EEG/EMG recordings to determine arousal states, we observed that population activity of GABAergic neurons in the lateral hypothalamus (LHGABA) is highest during rapid-eye-movement sleep (REM), and this activity changes drastically across spontaneous arousal state transitions, with the lowest activity observed during Non-REM sleep. Upon intraperitoneal LPS challenge, LHGABA neurons rapidly decrease their activity in tandem with elimination of REM sleep behavior (characteristic of cytokine-induced sickness). Together, these data suggest that peripheral immune challenges can rapidly (in < 40 min) alter subcortical neuronal circuits controlling arousal states. Additionally, we demonstrate that fiber photometry offers a sensitive and cell-type specific tool that can be applied to study the neuronal substrates of sickness behavior.